Birth preparedness complication readiness and determinants among pregnant women: a community-based survey from Ethiopia - Teshale Abosie Ananche; Legesse Tadesse Wodajo (BMC, 2020)
Abstract Background Maternal death related to obstetric complications remains a great challenge in developing countries. Since these complications are not consistently predictable, it is important to plan different preventive approaches to overcome them when. As the information on birth preparedness, complication readiness, and predictors were limited in the study area, we conducted this study. Methods A Cross-sectional study involving 396 pregnant women was conducted from 1st April to 1st May 2018. Data were collected using a pre-tested structured questionnaire. Descriptive, binary and multiple logistic regression analyses were conducted in SPSS for windows version 20. P values < 0.05 were considered significant. Results Of 361 women interviewed (91% response rate), birth preparedness and complication readiness were present in 24.10% (87/361) of women. Maternal factors, age 18-19 (AOR = 0.18; 95% CI (0.04,0.94)), 20-34 (AOR = 0.40; 95% CI (0.20,0.78)), education, not able to read/write (AOR = 0.36;95% CI (0.15,0.85),read/write (AOR = 0.41;95% CI (0.19,0.89)), Muslim religion (AOR = 0.40; 95% CI (0.18,0.85)) income ETB, < 1000 (AOR = 0.21; 95% CI (0.07,0.67)),1000-2000, (AOR = 0.38; 95% CI (0.19,0.76)), and the mothers' knowledge on key danger signs of postpartum (AOR = 0.48; 95% CI (0.26,0.90)) were independent predictors of birth preparedness and complication readiness. Conclusions Educational status, age, religion, family income, and knowledge of obstetric danger signs were significantly associated with birth preparedness and complication readiness. The Government and other health sector partners should work to improve women's education, income, and focus on young age groups on pregnancy danger signs.